ATF6 Is a Critical Determinant of CHOP Dynamics during the Unfolded Protein Response - Yang, Huan; Niemeijer, Marije; van de Water, Bob; Beltman, Joost B. (iScience, 2020)
The unfolded protein response (UPR) pathway senses unfolded proteins and regulates proteostasis and cell fate through activity of the transcription factors ATF4, ATF6, and XBP1 within a complex network of three main branches. Here, we investigated contributions of the three branches to UPR activity in single cells using microscopy-based quantification and dynamic modeling. BAC-GFP HepG2 reporter cell lines were exposed to tunicamycin, and activation of various UPR components was monitored for 24 h. We constructed a dynamic model to describe the adaptive UPR signaling network, for which incorporation of all three branches was required to match the data. Our calibrated model suggested that ATF6 shapes the early dynamics of pro-apoptotic CHOP. We confirmed this hypothesis by measurements beyond 24 h, by perturbing single siRNA knockdowns and by ATF6 measurements. Overall, our work indicates that ATF6 is an important regulator of CHOP, which in turn regulates cell fate decisions. [Display omitted] •A mathematical model of the unfolded protein response describes microscopy data•Integration of modeling and experimental work offers insights into UPR regulation•ATF6 shapes the early dynamics of the CHOP response Optical Imaging; Bioinformatics; Biocomputational Method; Systems Biology